Institutionalization, Framing, and Diffusion: The Logic of TQM Adoption and Implementation Decisions among U.S. Hospitals - Kennedy, Mark Thomas; Fiss, Peer Christian (Academy of Management Journal, 2009)
We extend institutional theory's account of diffusion by examining the interplay between economic and social considerations in adoption decisions. Drawing on organizational decision-making research, we argue that both early and late adopters respond to framing and interpreting adoption decision situations as opportunities versus threats. Using data on the diffusion of total quality management (TQM) among U.S. hospitals, we found that motivations to appear legitimate coexist with motivations to realize economic performance improvement, and that issue perception is related to the extent of practice implementation. These findings prompt rethinking of the classic institutional diffusion model.